ESTUDIOS SOBRE LA PONZONA DEL ALACRAN I INTRODUCCION DATOS ESTADISTICOS PARA SABER LA MORTALIDAD EN LA REPUBLICA - MENDEZ PEREZ, TH (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1949)
The morph and paleobiology of the Mexican spp of the bivalve genus Ptychomya are discussed 3 forms are recognized P mexicana n sp and P m var tehuacanensis n var, both from the vicinity of Tehuacan, Oaxaca (the former from other localities as
BOL INST ESTUD MED BIOL
Keywords: ESTUDIOS, PONZONA, ALACRAN, DATOS, ESTADISTICOS, MORTALIDAD; CIENCIAS MEDICAS; PATOLOGIA; PATOLOGIA CLINICA